Toward optimizing diversifying base editors for high-throughput mutational scanning studies - Schwartz, Carley I; Abell, Nathan S; Li, Amy; Aradhana; Tycko, Josh; Truong, Alisa; Montgomery, Stephen B; Hess, Gaelen T (Nucleic acids research, 2025)
Abstract Base editors, including diversifying base editors that create C>N mutations, are potent tools for systematically installing point mutations in mammalian genomes and studying their effect on cellular function. Numerous base editor options are available for such studies, but little information exists on how the composition of the editor (deaminase, recruitment method, and fusion architecture) affects editing. To address this knowledge gap, the effect of various design features, such as deaminase recruitment and delivery method (electroporation or lentiviral transduction), on editing was assessed across ∼200 synthetic target sites. The direct fusion of a hyperactive variant of activation-induced cytidine deaminase to the N-terminus of dCas9 (DivA-BE) produced the highest editing efficiency, ∼4-fold better than the previous CRISPR-X method. Additionally, DivA-BE mutagenized the DNA strand that anneals to the targeting sgRNA (target strand) to create complementary C>N mutations, which were absent when the deaminase was fused to the C-terminus of dCas9. Based on these studies that comprehensively analyze the editing patterns of several popular base editors, DivA-BE editors efficiently diversified their target sites, albeit with increased indel frequencies. Overall, the improved editing efficiency makes the DivA-BE editors ideal for discovering functional variants in mutational scanning assays. Graphical Abstract Graphical Abstract